Samarbetet mellan TNC och RTT 1938–1998: Terminologiarbete som resurs för meningsfull kommunikation - Landqvist, Hans; Nissilä, Niina; Pilke, Nina; Sjöberg, Sannina (VAKKI ry, 2023)
This article describes and analyses the contacts between the Swedish and Norwegian national terminology organisations between the 1940s and the 1990s. The Swedish Tekniska nomenklaturcentralen TNC (1941–2018; 2000–2018 Terminologicentrum TNC) was Sweden’s national center for special languages and terminology work for more than 75 years. Since its founding in 1941, the TNC was active not only in Sweden, but also in establishing and maintaining international contacts. The Norwegian Rådet for teknisk terminologi RTT was founded in 1938 and closed down in 2001. The research material used is the collection of correspondence in the TNC’s document archive, in particular the section stored with the code “Unor”, i.e., letters (N=374) documenting written communication between the TNC and the RTT. The article describes the topics covered in the communication, the individuals involved, the objectives and consequences of the communication and the results achieved. In a quantitative analysis, the themes of the letters are categorised in four main categories: publications, communication, information, and language issues. In a qualitative analysis, a specific terminological issue in the field of welding technology is analysed by close reading and content analysis. Finally, further studies, which complete the picture of terminological cooperation on institutional level in the Nordic countries, are proposed.
Keywords: domänförlust; domänvinst; Rådet for teknisk terminologi (RTT); Tekniska nomenklaturcentralen/Terminologicentrum (TNC); terminologi(sam)arbete; fi=Viestintätieteet|en=Communication Studies|